Influence of low-dose radiation on abscopal responses in patients receiving high-dose radiation and immunotherapy. Issue 1 (4th September 2019) - Menon, Hari; Chen, Dawei; Ramapriyan, Rishab; Verma, Vivek; Barsoumian, Hampartsoum B.; Cushman, Taylor R.; Younes, Ahmed I.; Cortez, Maria A.; Erasmus, Jeremy J.; de Groot, Patricia; Carter, Brett W.; Hong, David S.; et al.
Abstract : Background: Preclinical evidence suggests that low-dose radiation may overcome the inhibitory effects of the tumor stroma and improve a tumor's response to immunotherapy, when combined with high-dose radiation to another tumor. The aim of this study was to evaluate tumor responses to this combination in a clinical setting. Methods: A post-hoc analysis of 3 ongoing immunoradiation trials was performed. Twenty-six (of 155) patients received low-dose radiation (1–20 Gy total), either as scatter from high-dose radiation or from intentional treatment of a second isocenter with low-dose radiation, were evaluated for response. The low-dose lesions were compared to lesions that received no radiation (< 1 Gy total). Response rates, both defined as complete and partial responses as defined by RECIST criteria were used to compare lesion types. Results: The 26 patients had a total of 83 lesions for comparison (38 receiving low-dose, 45 receiving no-dose). The average dose given to low-dose lesions was 7.3 Gy (1.1–19.4 Gy), and the average time to response was 56 days. Twenty-two out of 38 (58%) low-dose lesions met the PR/CR criteria for RECIST compared with 8 out of 45 (18%) no-dose lesions ( P = 0.0001). The median change for longest diameter size for low-dose lesions was − 38.5% compared to 8% in no-dose lesions ( P < 0.0001). Among the low-dose lesions that had at least one no-dose lesion within the same patient as a control (33 and 45 lesions respectively), 12 low-dose lesions (36%) responded without a corresponding response in their no-dose lesions; Conversely, two (4%) of the no-dose lesions responded without a corresponding response in their low-dose lesion ( P = 0.0004). Conclusions: Low-dose radiation may increase systemic response rates of metastatic disease treated with high-dose radiation and immunotherapy.